2017
DOI: 10.21082/jp3.v36n1.2017.p28-38
|View full text |Cite
|
Sign up to set email alerts
|

Budidaya Padi Di Lahan Rawa Pasang Surut Dan Pengaruhnya Terhadap Penggerek Batang Padi

Abstract: <p>Rice cultivation in tidal swampland of South Kalimantan has been practiced by farmers in the long period and influences the population of rice stem borer. This paper describes rice cultivation in tidal swampland of South Kalimantan and its impact on injury level caused by rice stem borer. Land preparation by slashing and spinning the rest of rice crop and then left it to rot, can thwart rice stem borer larvae to become imago (adult). Seeding by transplanting several times can kill stem borer larvae, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 5 publications
0
3
0
4
Order By: Relevance
“…[11][12][13] This high antioxidant activity promotes wound healing because it stimulates the production of endogenous antioxidants at the wound site and provides an environment conducive to wound healing. 10, 14 In the early stages of the wound healing process, there will be an inflammatory phase and the formation of reactive oxygen species (ROS) produced by neutrophils and macrophages as part of the immune system to help accelerate wound cleansing. Apart from its positive effect, ROS also has a negative impact.…”
Section: Original Articlementioning
confidence: 99%
See 1 more Smart Citation
“…[11][12][13] This high antioxidant activity promotes wound healing because it stimulates the production of endogenous antioxidants at the wound site and provides an environment conducive to wound healing. 10, 14 In the early stages of the wound healing process, there will be an inflammatory phase and the formation of reactive oxygen species (ROS) produced by neutrophils and macrophages as part of the immune system to help accelerate wound cleansing. Apart from its positive effect, ROS also has a negative impact.…”
Section: Original Articlementioning
confidence: 99%
“…13 Furthermore, several other studies have shown that Chromolaena odorata leaf extract can inhibit the growth of Staphylococcus aureus found in wounds. 14 However, to date, there has been no study proving that Chromolaena odorata with different bases as jelly can accelerate the healing of open wounds, especially in the early phase. This condition encourages the author to study the effect of Chromolaena odorata leaf jelly extract on wound healing in the inflammatory and proliferative phases of white rats (Rattus norvegicus).…”
Section: Introductionmentioning
confidence: 99%
“…Tumbuhan ini dengan kandungan senyawa kimia di dalamnya mampu berfungsi untuk menarik atau mengumpan serangga dan hewan lain yang dapat menganggu tanaman (Pyenson, 1980). Menurut Thamrin et al (2017), kerusakan padi yang dikarenakan hama Scirpophaga innotata (PBP putih), yang tumbuh berdekatan dengan gulma purun tikus akan lebih rendah karena hama Scirpophaga innotata (PBP putih) akan tertarik untuk menaruh telurnya pada gulma purun tikus. Asikin dan Thamrin (2012) membuktikan bahwa penyemprotan tanaman padi dengan ekstrak Eleocharis dulcis mampu lebih banyak memerangkap hama Scirpophaga innotata dibanding tumbuhan lain seperti tumbuhan wlingi (Scirpus grosus), purun danau (Lepironea articulate), lemiding (Stenochlaena palutris), dan perumpung (Phragmites karka).…”
Section: Upayaunclassified
“…Penggunaan varietas lokal berumur dalam hingga 6 bulan menjadi kendala peningkatan IP. Alternatif untuk peningkatan IP menjadi dua kali dalam setahun (IP200) dapat dilakukan dengan penerapan kombinasi varietas lokal dan VUB (Thamrin et al, 2017). Karakter umur yang dapat diidentifikasi melalui umur berbunga (Jiang et al, 2018), menjadi isu penting dalam melakukan pendekatan pada peningkatan produktivitas dan IP di lahan rawa pasang surut.…”
unclassified